2010
DOI: 10.2215/cjn.06720810
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant Recurrence of Primary Glomerulonephritis

Abstract: All forms of primary GN may recur after kidney transplantation and potentially jeopardize the survival of the graft. IgA nephritis (IgAN) may recur in approximately one third of patients, more frequently in younger patients and in those with a rapid progression of the original disease. However, with the exception of few patients with rapid progression, there is no evidence that recurrence of IgAN has a deleterious effect on graft survival at least up to 10 years. Recurrence of focal segmental glomerulosclerosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
171
2
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(184 citation statements)
references
References 127 publications
7
171
2
4
Order By: Relevance
“…29 Similar findings were found in other studies, such as that by Lorenz and associates who reported nearly similar results to the latter. 30 The major difference between our study and others may be due to presence of larger number of patients (1321 patients) and also to difference in study methodology, as Lorenz and colleagues used a protocol biopsy in detection of recurrence, whereas in our study only event biopsy was carried out.…”
Section: Discussionsupporting
confidence: 90%
“…29 Similar findings were found in other studies, such as that by Lorenz and associates who reported nearly similar results to the latter. 30 The major difference between our study and others may be due to presence of larger number of patients (1321 patients) and also to difference in study methodology, as Lorenz and colleagues used a protocol biopsy in detection of recurrence, whereas in our study only event biopsy was carried out.…”
Section: Discussionsupporting
confidence: 90%
“…The use of RTX in primary FSGS in adults has had variable, but mostly negative results in small case series [90], [91] and [92]. However, it may be useful in treating posttransplant relapse [93], [94] and [95]. Interestingly, recent research has shown that RTX may have a direct effect on podocytes, regardless of its action on B-cells, and this could explain the beneficial effect of RTX in these nephrotic disorders that are not clearly associated with auto-antibodies [96].…”
Section: Focal Segmental Glomerulosclerosis and Minimal Change Diseasementioning
confidence: 99%
“…Two patterns of clinical presentations are observed: Early recurrence, which is most commonly encountered in pediatric patients and characterized by a massive proteinuria that occurs within hours to days after implantation of the new kidney; late recurrence, which often develops insidiously at several months to years after the transplantation [9] . Many clinical conditions have been recognized as risk factors for recurrence [4,8,10] , including younger age (particularly in children who were > 6-year-old at FSGS onset), mesangial proliferation in the native kidneys, rapid progression of the disease to endstage renal disease (ESRD; < 3 years from onset) for native kidneys, pre-transplant bilateral nephrectomy, non-African race, specific genetic background, heavy proteinuria before transplantation, and, as cited above, loss of previous allografts due to recurrence.…”
Section: Introductionmentioning
confidence: 99%